Non-invasive diagnosis of mitral regurgitation by Doppler echocardiography. Issue 5 (May 1981) - Blanchard, D; Diebold, B; Peronneau, P; Foult, J M; Nee, M; Guermonprez, J L; Maurice, P
Abstract : The value of Doppler echocardiography for the non-invasive diagnosis of mitral regurgitation was studied blindly in 161 consecutive invasively investigated adult patients. Regurgitation was graded from 0 to 3 at selective left ventricular angiography. The Doppler echocardiographic examination was considered to be positive when a disturbed systolic flow was found within the left atrium behind the aorta or the anterior leaflet of the mitral valve. The test was considered to be negative in the absence of a regurgitant jet. The level of the signal to noise ratio was checked by the recording of the ventricular filling flow. The study was performed in 131 cases from the left side of the sternum and in 101 cases from the apex. There were no false positives and thus the specificity was 100 per cent. The 20 false negatives were all in patients with grade 1 regurgitation. Thus only some (33%) instances of mild regurgitation were misdiagnosed, and the sensitivity for moderate to severe mitral regurgitation was 100 per cent.